THE ROLE OF THE INTEGRATIVE APPROACH IN DEVELOPING THE LOGICAL THINKING ABILITIES OF STUDENTS IN FUTURE PRIMARY SCHOOL TEACHERS - Toshpulatova Durdona Komiljon qizi (Web of Journals Publishing, 2025)
To develop students' logical thinking skills and strengthen their interest in studying general education subjects through conducting small educational research, practical exercises were included in the subject curriculum. These practical exercises not only improve the quality of learning in a specific academic discipline, but also open up opportunities for interdisciplinary and scientific connections with daiyly life and increase the effectiveness of learning.
Keywords: Integration, independence of thinking, quickness of resourcefulness in solving logical tasks, speed and strength of learning material assimilation, ability to distinguish what is important from what is not important. critical thinking.